Pengaruh Penggunaan Kosmetik (Whitening Cream) Terhadap Kadar Merkuri (Hg) Pada Perawat Magang Program Studi Profesi Ners Universitas Muslim Indonesia - Yusuf, Nurfadhilah; Wahyu, Atjo; Habo, Hasriwiani (Window of Health : Jurnal Kesehatan, 2019)
A number of cosmetics allegedly contain mercury added with the aim of reducing black stains on the surface of the skin. This study aims to analyze the effect of cosmetic use (whitening cream) on Hg levels in the UMI Nurse Internship profession. Sampling using purposive sampling method, the population in this study were nurses profession internship nurses from the Indonesian Muslim University who used a total of 90 people, researchers determined a total sample of 61 people namely nurses Internship profession Study Program UMI generation V as many as 20 people and VI generation nurses as many as 41 people, data analysis using correlation analysis, Pearson test and T test with Î± = 0.05. The results showed that the average mercury level using whitening cream was 0.33 ppm and not users cosmetics of whitening cream 0.18 ppm, with mercury levels from the lowest to highest incosmetic wearers whitening for 0.04-2 ppm and non-cosmetic whitening creams amounted to 0.07-0.36 ppm, this indicates that there are differences in the effect of Hg levels on hair on users of cosmetics whitening cream and non-.cosmetic User whitening cream (pvalue 0,000), the effect on the volume of Hg levels (pvalue 0,000), no influence on the frequency of Hg ( p value of 0.000), there is the influence of the duration of use of the Hg value of 0.001, while not influential, namely age, the form of cosmetics whitening cream and the complaints of users whitening cream against level Hg, given the presence of metal brand uri contained in the whitening cream sample, it is expected that users of cosmetics whitening cream should be more careful in choosing whitening cosmetics.